Financial Education, Illegal Loans, Rural Msmes, Financial Literacy: Pengabdian - Satria Putra Utama; Muhammad Simba Sembiring; Afrizal; Raihan Hanasi; Maya Kasmita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in rural areas play a crucial role as the backbone of the domestic economy. However, limited financial literacy and difficult access to formal financial institutions often trap MSMEs in a vicious cycle of illegal online loans (illegal pinjol) and loan sharks. This community service activity aims to improve understanding of financial management and educate rural MSMEs about the fatal risks of illegal loans. The "Financial Planning Education" education program was implemented simultaneously in three representative regions of Indonesia, namely the provinces of North Sumatra, East Java, and Sulawesi (South Sulawesi and North Sulawesi). The activity implementation method used a participatory approach that included three main stages: (1) Socialization and classical education on family and business financial planning; (2) Training in identifying the characteristics of legal vs. illegal loans; and (3) Assistance in utilizing fintech platforms registered with the Financial Services Authority (OJK). The results of the evaluation through pre-test and post-test showed a significant increase in partners' understanding of financial literacy by 78%. Furthermore, MSMEs are now able to prepare simple financial reports and have legal awareness to avoid the pitfalls of illegal loans. The sustainability of this program is expected to foster an independent, resilient, and financially savvy village MSME ecosystem.